Analisis Kitab Adab Al-Mufrad Karya Imam Bukhari Tentang Pendidikan Adab dan Relevansinya terhadap Pendidikan Karakter di Indonesia - Nurhadi Nurhadi; Alfen Khairi (PALAPA, 2020)
Islamic education aims to print students into intellectuals who are both intellectually intelligent and morally good. To achieve these educational goals, the morals and manners of the spirit of education need to be revived. In addition, Islamic education must also isolate the secular-liberal view of life that exists in every modern scientific discipline. Such education will give birth to humans who are aware of their responsibilities towards their Lord, understand and carry out their obligations to themselves and others in their society, and strive continuously to develop every aspect of themselves towards advancement as moral human beings. To achieve this goal, the Indonesian government rolled out character education. Character education is expected to be able to balance between the fulfillment of cognitive needs with other needs as mandated by the 2003 National Education System Law. Similarly, Islamic education is already familiar with the concept of etiquette. This study aims to determine the concept of etiquette education according to Imam Bukhari in the book of Adab Al Mufrad and to make it relevant with character education in Indonesia. In this study it was found that the concept of education according to Imam Bukhari includes adab to parents, adab to children, adab to others, adab to Allah, and adab to the prophet Muhammad. This concept of etiquette covers the five pillars of the value of character education in Indonesia and can be used as a foothold in describing the values ​​of education that are being practiced in Indonesia.